The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3897/phytokeys.190.77918
|View full text |Cite
|
Sign up to set email alerts
|

Maxillaria anacatalinaportillae (Orchidaceae, Maxillariinae), a new remarkable species from Ecuador

Abstract: Neotropical genus Maxillaria Ruiz & Pav. belongs to one of the most diverse and species-rich groups of orchids. Several of its representatives are popular, horticultural plants with large and showy flowers, often nicely fragranced. It is not uncommon that some distinctly colored individuals are introduced to the commercial market under names of similar, more or less related species, as informal varieties or color forms, largely causing confusion. While investigating the diversity of Maxillaria in Ecuad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Maxillaria Ruiz & Pav. sensu lato is one of the most diverse orchid genera in the world, embracing about 651 species (Christenson et al 2012, Engels & Smidt 2023, Lipińska et al 2022, Schuiteman & Chase 2015. Plants of Maxillaria grow as epiphytes, lithophytes, or terrestrials in cloudy, wet, or more rarely in seasonally dry forests, from the United States (Florida) and Mexico to northern Argentina, including the Antilles (Schuiteman & Chase 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Maxillaria Ruiz & Pav. sensu lato is one of the most diverse orchid genera in the world, embracing about 651 species (Christenson et al 2012, Engels & Smidt 2023, Lipińska et al 2022, Schuiteman & Chase 2015. Plants of Maxillaria grow as epiphytes, lithophytes, or terrestrials in cloudy, wet, or more rarely in seasonally dry forests, from the United States (Florida) and Mexico to northern Argentina, including the Antilles (Schuiteman & Chase 2015).…”
mentioning
confidence: 99%
“…The Andean countries of northern South America are the richest in Maxillaria species. Colombia and Ecuador together have more than 400 species recorded (Govaerts et al 2021, Ortiz Valdivieso & Uribe Vélez 2007, with several new species discovered and described in the last years (Moreno et al 2017, Szlachetko et al 2017, Zambrano-Romero et al 2020Lipińska et al 2022). Nonetheless, taxonomic studies for Maxillaria remain scarce in both countries, and new species can still be found (Zambrano-Romero & Solano-Gómez 2016).…”
mentioning
confidence: 99%